Synthesis, structure, thermostability and luminescence properties of ZnII and CdII coordination polymers based on dimethysuccinate and flexible 1, 4‐bis(imidazol‐1‐ylmethyl)benzene ligands. Issue 9 (10th August 2016) - Liu, Yang; Feng, Yong-Lan; Fu, Wei-Wei
Abstract : Two d 10 coordination polymers of Zn II and Cd II based on 2, 2‐dimethylsuccinate and flexible 1, 4‐bis(imidazol‐1‐ylmethyl)benzene as coligands have been synthesized under hydrothermal conditions. Both complexes display a two‐dimensional layered architecture and were characterized by elemental analysis, X‐ray crystallography, IR spectroscopy and thermogravimetric analysis. They also display a strong blue photoluminescence in the solid state at room temperature. Abstract : The design and synthesis of functional coordination polymers is motivated not only by their structural beauty but also by their potential applications. Zn II and Cd II coordination polymers are promising candidates for producing photoactive materials because these d 10 metal ions not only possess a variety of coordination numbers and geometries, but also exhibit luminescence properties when bound to functional ligands. It is difficult to predict the final structure of such polymers because the assembly process is influenced by many subtle factors. Bis(imidazol‐1‐yl)‐substituted alkane/benzene molecules are good bridging ligands because their flexibility allows them to bend and rotate when they coordinate to metal centres. Two new Zn II and Cd II coordination polymers based on mixed ligands, namely, poly[[μ2 ‐1, 4‐bis(imidazol‐1‐ylmethyl)benzene‐κ 2 N 3 : N 3′ ]bis(μ3 ‐2, 2‐dimethylbutanoato‐κ 3 O 1 : O 4 : O 4′ )dizinc(II)], [Zn2 (C6 H8 O4 )2 (C14 H14 N4 )] n, and poly[[μ2 ‐1, 4‐bis(imidazol‐1‐ylmethyl)benzene‐κ 2 N 3 : N 3′ ]bis(μ3 ‐2, 2‐dimethylbutanoato‐κ 5 O 1, O 1′ : O 4, O 4′ : O 4 )dicadmium(II)], [Cd2 (C6 H8 O4 )2 (C14 H14 N4 )] n, have been synthesized under hydrothermal conditions and characterized by single‐crystal X‐ray diffraction, elemental analysis, IR spectroscopy and thermogravimetric analysis. Both complexes crystallize in the monoclinic space group C 2/ c with similar unit‐cell parameters and feature two‐dimensional structures formed by the interconnection of S‐shaped Zn(Cd)–2, 2‐dimethylsuccinate chains with 1, 4‐bis(imidazol‐1‐ylmethyl)benzene bridges. However, the Cd II and Zn II centres have different coordination numbers and the 2, 2‐dimethylsuccinate ligands display different coordination modes. Both complexes exhibit a blue photoluminescence in the solid state at room temperature.